Dydrogesterone-induced hepatitis and autoimmune hemolytic anemia - Engin ALTINTAŞ; Dilek OĞUZ; Sabite KACAR; Yasemin ÖZDERİN ÖZİN and Orhan SEZGİN and Neslihan İNCİ ZENGİN (Turkish Journal of Gastroenterology, 2019)
-